1991
DOI: 10.1038/352809a0
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for mast cell growth factor for primordial germ cell survival in culture

Abstract: Mast-cell growth factor (MGF) is encoded by the murine steel (Sl) locus and is a ligand for the tyrosine kinase receptor protein encoded by the proto-oncogene c-kit at the murine dominant white spotting (W) locus. Mutations at both these loci affect mast cells, primordial germ cells (PGCs), haemopoietic stem cells and melanocytes. In many Sl and W mutants, the rapid proliferation of PGC that normally occurs between day 7 and 13.5 of embryonic development fails to occur. As c-kit is expressed in PGCs while MGF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
230
0
3

Year Published

1992
1992
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 467 publications
(237 citation statements)
references
References 23 publications
4
230
0
3
Order By: Relevance
“…Notably, the first Kit intron was previously shown to be essential for Kit expression in these cells as well as in hematopoietic precursors [22,47]. Since Kit signaling is essential for survival and proliferation of germ cells [25,27,48], we can hypothesize that one of the mechanisms by which Sox2 ablation affects PGCs is through downregulation of Kit transcription. Although it is generally accepted that Kit is not strictly required for the establishment of the germline [49], more recent work has shown that PGCs are dependent on Kitl expression from the surrounding environment as early as at the time of their specification [50].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, the first Kit intron was previously shown to be essential for Kit expression in these cells as well as in hematopoietic precursors [22,47]. Since Kit signaling is essential for survival and proliferation of germ cells [25,27,48], we can hypothesize that one of the mechanisms by which Sox2 ablation affects PGCs is through downregulation of Kit transcription. Although it is generally accepted that Kit is not strictly required for the establishment of the germline [49], more recent work has shown that PGCs are dependent on Kitl expression from the surrounding environment as early as at the time of their specification [50].…”
Section: Discussionmentioning
confidence: 99%
“…One of these genes is Kit, which encodes the tyrosine-kinase receptor for Kit Ligand (Kitl), essential for PGCs development [27]. Sox2 overexpression in ES cells has been shown to induce high levels of Kit mRNA, as evaluated by microarray analysis [38].…”
Section: Sox2 Is Expressed In Postnatal Oocytes But Is Not Essential mentioning
confidence: 99%
See 1 more Smart Citation
“…However, mice with this mutation are anemic, sterile, and have altered pigmentation. Other experiments performed in vitro demonstrate that membrane-anchored kit-ligand supports primordial germ cell growth, whereas soluble kit-ligand does not (Dolci et al, 1991). Thus, the physiological consequences of the Sld mutation probably reflect the requirement of a membranebound form of kit-ligand in normal development.…”
Section: Regulation In Time and Spacementioning
confidence: 99%
“…KL stimulates colony formation of primitive hematopoietic precursors from bone marrow (Metcalf and Nicola, 1991) and induces the proliferation of mast cells (Tsai et al, 1991). Like somatic cells, primordial germ cells, which express Kit receptors, respond to KL in culture with increased survival (Dolci et al, 1991;Godin et al, 1991;Pesce et al, 1993) and proliferation (Matsui et al, 1991). In prepubertal male mice, KL selectively stimulates DNA synthesis in type A spermatogonia (Rossi et al, 1993).…”
Section: Introductionmentioning
confidence: 99%